Clinical features of haematospermia associated with seminal vesicle calculi versus posterior urethral haemangioma. (25th June 2018) - Tian, Long; Han, Hu; Lei, Hong‐en; Zhang, Xiao‐dong
Abstract: To compare the clinical features of seminal vesicle calculi(SVC) versus posterior urethral haemangioma(PUH) to assist urologists in differentiating and diagnosing the causes of haematospermia. Patients with SVC or PUH were included. Patient age, disease duration, hospital stay, operation time, symptoms, surgical approach, pathological results and postoperative complications were recorded. A total of seven patients with SVC and 15 patients with PUH involved have an average age of 34.1 and 44.5 years separately. Patients with SVC complained of recurrent haematospermia; patients with PUH complained of recurrent haematospermia and urethral opening bleeding after sexual arousal. SVC manifested as a dark red blood–semen mixture with ejaculation pain and no blood clots; the condition could improve after anti‐infective treatment. PUH manifested as no visible blood–semen mixture, bright red semen with blood clots and no ejaculation pain; the condition did not respond to anti‐infective treatment. SVC was treated with holmium laser lithotripsy under a transurethral seminal vesiculoscopy. PUH was treated with transurethral resection and fulguration. Postoperative follow‐up showed that the clinical symptoms gradually disappeared, with no postoperative complications. Both SVC and PUH can result in recurrent haematospermia. Therefore, urologists should treat haematospermia differently according to the cause.